2013
DOI: 10.1021/jo400550c
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigations on Base-Catalyzed Diaryl Ether Formation

Abstract: We report investigations with the dispersion-corrected B3LYP density functional method on mechanisms and energetics for reactions of group I metal phenoxides with halobenzenes as models for polyether formation. Calculated barriers for ether formation from para-substituted fluorobenzenes are well correlated with the electron-donating or -withdrawing properties of the substituent at the para position. These trends have also been explained with the distortion/interaction energy theory model which show that the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 77 publications
0
33
0
Order By: Relevance
“…[20] However, their calculations revealed that presence of M + ions increases the barrier height due to formation of stable reactant complexes upon interaction with the fluorobenzenes. [20] Our experimental results, shown in Table 1, appear to be consistent with the computational results reported by Jones et al, since M + ions (except 18C6-crowned K + ion) inhibit the reaction of 7 a and the inhibitory effect increases as the size of www.chemeurj.org M + ions decreases. [20] Our experimental results, shown in Table 1, appear to be consistent with the computational results reported by Jones et al, since M + ions (except 18C6-crowned K + ion) inhibit the reaction of 7 a and the inhibitory effect increases as the size of www.chemeurj.org M + ions decreases.…”
Section: Comparison To Computational Studymentioning
confidence: 99%
See 2 more Smart Citations
“…[20] However, their calculations revealed that presence of M + ions increases the barrier height due to formation of stable reactant complexes upon interaction with the fluorobenzenes. [20] Our experimental results, shown in Table 1, appear to be consistent with the computational results reported by Jones et al, since M + ions (except 18C6-crowned K + ion) inhibit the reaction of 7 a and the inhibitory effect increases as the size of www.chemeurj.org M + ions decreases. [20] Our experimental results, shown in Table 1, appear to be consistent with the computational results reported by Jones et al, since M + ions (except 18C6-crowned K + ion) inhibit the reaction of 7 a and the inhibitory effect increases as the size of www.chemeurj.org M + ions decreases.…”
Section: Comparison To Computational Studymentioning
confidence: 99%
“…[20] Their calculations using DFT methods have shown that M + ions (M + = Li + , Na + , and K + ) complex the fluoride leaving group and facilitate expulsion of the leaving group as modeled by TS III in Scheme 4. [20] Their calculations using DFT methods have shown that M + ions (M + = Li + , Na + , and K + ) complex the fluoride leaving group and facilitate expulsion of the leaving group as modeled by TS III in Scheme 4.…”
Section: Comparison To Computational Studymentioning
confidence: 99%
See 1 more Smart Citation
“…19 Thus, one might suggest that the current reaction would proceed also through a cyclic intermediate as modeled by IV. It is apparent that expulsion of the leaving group from IV could be facilitated through the H-bonding interaction.…”
mentioning
confidence: 99%
“…Recently, Jones et al have carried out computational investigations on the S N Ar reaction of activated fluorobenzenes with alkali-metal phenoxides. 12 The results their DFT calculations have shown that the presence of alkali-metal ion does not increase the rate of reaction but plays an important role through TS IV , in which M + ion facilitates expulsion of the leaving group.…”
mentioning
confidence: 99%